Systemic Pseudohypoaldosteronism Type I: A Case Report and Review of the Literature. (18th April 2017) - Nur, Nasifa; Lang, Cameron; Hodax, Juanita K.; Quintos, Jose Bernardo
Abstract : Systemic pseudohypoaldosteronism (PHA) type I is a rare genetic disorder resulting from mutations in the subunits of the epithelial sodium channel that manifests as severe salt wasting, hyperkalemia, and metabolic acidosis in infancy. In this article we report a patient with systemic PHA type I presenting with severe dehydration due to salt wasting at 6 days of life. She was found to have a known mutation in the SCNN1A gene and subsequently required treatment with sodium supplementation. We also review the clinical presentation, differential diagnosis, and treatment of systemic PHA type I and summarize data from 27 cases with follow-up data.